Psychological Skills Training (PST) and Socioeconomic Equity: An Experimental Study on Bridging the Performance Gap and Addressing the Incomplete Athlete Syndrome in Kashmiri Sportspersons - Muhammad Owais Isaac (Feelings: Journal of Counseling and Psychology, 2026)
This study delves into a critical oversight in the development of sports talent within regions like Kashmir: the profound neglect of psychological conditioning. The paper proposes that the exceptional mental toughness traditionally observed in successful athletes from humble socioeconomic backgrounds is not accidental; rather, it is an organic by-product of life struggle and heightened responsibility. This “struggle-forged” resilience provided a powerful, albeit unintentional, competitive edge over affluent counterparts, whose lives are often described as an ”almost smooth line.” However, the dramatic shift in the 21st century, where affluent athletes are achieving success with increased regularity, points directly to their access to formalized Psychological Skills Training (PST). The prevailing coaching methodologies in Kashmir suggest that mental skills training should begin only after a certain age (often post-Under-14) or assume that psychological strength develops naturally through experience and game exposure. This paper challenges and effectively renders this approach obsolete as the accelerated pace of modern sport sees most athletes now representing states and nations at elite levels well before teenage years. Thus, the days are gone when athletes had plenty of years and low competition to experiment and learn through trial and error. To investigate this, the study draws on both observational data and an experimental intervention at the Modern Cricket Institute Bijbehara (MCI Bijbehara) and Jammu and Kashmir Sports Council Academy Unit Bijbehara (JKSCSK Bijbehara). Self-report measures using the Athletic Coping Skills Inventory-28 (ACSI-28) and the Competitive State Anxiety Inventory-2 (CSAI-2) were employed across a sample of athletes ranging from under-14 to senior categories. Building on these findings, the research introduces the concept of “Incomplete Athlete Syndrome,” where athletes are technically proficient but psychologically underdeveloped, leading to performance breakdowns under pressure. The data reveal that psychological skills are effective and teachable even during early developmental years, strongly contradicting the existing coaching paradigm in Kashmir. Experimental interventions at both institutes substantiates the hypothesis, demonstrating that early integration of mental skills training significantly improves psychological resilience and competitive performance. In conclusion, this paper advocates for the urgent and universal inclusion of mental skills training alongside technical development from the earliest stages of athlete preparation. Psychological resilience, confirmed as a teachable and essential skill, is critical to developing well-rounded, pressure-ready athletes capable of thriving in today’s demanding competitive sports environment.